Return migration and labour market outcomes of the returnees. Does the return really pay off? The case-study of Romania and Bulgaria - Isilda Shima (FIW - Research Centre International Economics, 2010)
In this study we analyse the labour market performance of Romanian and Bulgarian return migrants and whether it really pays off to return home. We looked at the employment dynamics of returnees from the perspective of employment and occupational status switches to capture the effects of the work experience abroad on the upgrade in the home labour market. After predicting the wages and measuring the wage premium upon return, we apply an endogenous switching ordered probit model to estimate simultaneously the decision to migrate temporarily and the determinants of an upgrading of labour market performance upon return. The labor market performance of return migrants is analysed by using the 2005 World Bank Surveys in Bulgaria and Romania. The main conclusion is that the interdependence in the decision-making between return migration and labour market participation requires counting them simultaneously. While, the labour market participation upon return are strongly determined by the intentions of a permanent return and the expectation of return premiums for the skills and experience acquired abroad, the permanent intentions of return are determined by the experience abroad, the family ties and by intentions of other household members to migrate.
Keywords: F22; J24; J61; 330; return migration; wage premium; occupational upgrading